Mechanical Response of Typical Cement Concrete Pavements under Impact Loading. (16th January 2017) - Fei, Ding; Yan, Yin; Liangcai, Cai; Yaohong, Tang; Xuancang, Wang
Abstract : In order to study the mechanical response of cement concrete pavements under impact loading, four types of typical cement concrete pavement structures are investigated experimentally and numerically under an impact load. Full-scale three-dimensional pavement slots are tested under an impact load and are monitored for the mechanical characteristics including the deflection of the pavement surface layer, the strain distribution at the bottom of the slab, and the plastic damage and cracking under the dynamic impact load. Numerical analysis is performed by developing a three-dimensional finite element model and by utilizing a cement concrete damage model. The results show that the calculation results based on the cement concrete damage model are in reasonable agreement with the experimental results based on the three-dimensional test slot experiment. The peak values of stress and strain as monitored by the sensors are analyzed and compared with the numerical results, indicating that the errors of numerical results from the proposed model are mostly within 10%. The rationality of the finite element model is verified, and the model is expected to be a suitable reference for the analysis and design of cement concrete pavements.